Eosinophilic gastroenteritis in an elderly men associated with antibiotic use post maxillofacial space infection: a case report - Lin, Ran; Ye, Kangjie; Hong, Min; Li, Jiqiang; Zhang, Zhongde; Zhang, Xi (Frontiers in Medicine, 2024)
A 79-year-old man underwent operative drainage and 2-week cephalosporin treatment due to a maxillofacial space infection (bilateral submaxillaris, submentum, and left face). However, he experienced anorexia, nausea, vomiting, and emaciation in the following 2 months. It was initially considered that a malignancy might be present, thus a series of examinations were performed.Laboratory investigations showed increases in inflammatory markers and a significant eosinophilia, which seemed to be a hematological system disease. Combined with the gastrointestinal endoscopes and histology examination, the patient was diagnosed with eosinophilic gastroenteritis (EGE). After cessation of antibiotic treatment and administration of corticosteroid, our patient experienced a rapid progress in his clinical condition. Despite the low incidence, EGE should be considered in patients with unknown cause of gastrointestinal disorder, elevated eosinophilia, and so on.